2023
DOI: 10.1002/jclp.23479
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of therapeutic interventions on psychological distress in refugee children: A systematic review

Abstract: Objective To systematically review existing research exploring the effectiveness of psychological interventions in reducing symptoms of distress amongst refugee and asylum‐seeker children. Method Six databases were searched to identify English studies presenting original empirical quantitative data (published before September 2022) testing the efficacy of psychological interventions for children from refugee and asylum‐seeking backgrounds. Quality of studies were assessed through the Appraisal Tool for Cross‐S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 93 publications
0
9
0
Order By: Relevance
“…The increase in RCTs and controlled studies is indicative of that. Thus, as Cowling and Anderson [ 21 ] also pointed out, the findings are very promising; nevertheless, it is still difficult to draw conclusions in terms of effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The increase in RCTs and controlled studies is indicative of that. Thus, as Cowling and Anderson [ 21 ] also pointed out, the findings are very promising; nevertheless, it is still difficult to draw conclusions in terms of effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…We opted to include papers included in previous reviews within our own review rather than move on from them because of differences in the inclusion criteria adopted by different reviews. The systematic review of Cowling and Anderson [ 21 ] was not scanned for the literature, as it was published while this paper was being written.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is systematic review evidence from RCTs that providing psychosocial interventions to refugees is effective in reducing PTSD symptoms 382 . Encouragingly, brief in dividual 383 or groupbased 384,385 psychological and behavioural interventions appear to reduce depressive and internalizing symp toms in refugees, including children 386 and adolescents 384 , though these may not be sustained in the longterm postinter vention 385 , and some evidence is of low quality 386 . A recent systematic review also found evidence that communitybased inter ventions which provided refugees with greater bridging and linking social capital (i.e., building ties with others in the community, helping them nav igate new structures, systems and institutions) may be most effec tive in reducing mental health symptoms in this population 387 .…”
Section: Public Mental Health Interventions For Specific Populationsmentioning
confidence: 99%